Substructuring of dynamical systems via the adaptive minimal control synthesis algorithm. - Wagg, D.J.
In this paper we consider the concept of modelling dynamical systems using numerical-experimental substructuring. This type of modelling is applicable to large or complex systems, where some part of the system is difficult to model numerically. The substructured model is formed via the adaptive minimal control synthesis (MCS) algorithm. The aim of this paper is to demonstrate that substructuring can be carried out in real time, using the MCS algorithm. Thus, we reformulate the MCS algorithm into a substructuring form. We introduce the concepts of a transfer system, and carry out numerical simulations of the substructuring process using a coupled three mass example. These simulations are compared with direct simulations of a three mass system. In addition we consider the stability of the substructuring algorithm, which we discuss in detail for a class of second order transfer systems. A numerical experimental system is considered, using a small scale experimental system, for which the substructuring algorithm is implemented in real time. Finally we discuss these results, with particular reference to the future application of this method to modelling large scale structures subject to earthquake excitation.
Keywords: Adaptive control; Numerical experimental substructuring; Real time control; Modelling large structures; Earthquake excitation